2021
DOI: 10.1002/hep.31875
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate Receptor 5 in Natural Killer Cells Attenuates Liver Fibrosis by Exerting Cytotoxicity to Activated Stellate Cells

Abstract: Background and Aims The important roles of glutamate and metabotropic glutamate receptor 5 (mGluR5) in HSCs have recently been reported in various liver diseases; however, the mechanism linking the glutamine/glutamate metabolism and mGluR5 in liver fibrosis remains unclear. Here, we report that mGluR5 activation in natural killer (NK) cells attenuates liver fibrosis through increased cytotoxicity and interferon‐γ (IFN‐γ) production in both mice and humans. Approach and Results Following 2‐week injection of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…IFN-γ not only inhibits HSC activation and ECM synthesis directly ( 20 ) but also amplifies NK-cell cytotoxicity against HSCs by promoting NKG2D expression on liver NK cells to attenuate liver fibrosis ( 21 ). A decreased frequency of NK cells with a reduction of function can be observed in the liver of both murine cirrhotic models ( 22 ) and cirrhotic patients ( 4 , 23 , 24 ). In this study, the proportion of the NK cluster cells decreased significantly in the cirrhotic group, which was consistent with previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ not only inhibits HSC activation and ECM synthesis directly ( 20 ) but also amplifies NK-cell cytotoxicity against HSCs by promoting NKG2D expression on liver NK cells to attenuate liver fibrosis ( 21 ). A decreased frequency of NK cells with a reduction of function can be observed in the liver of both murine cirrhotic models ( 22 ) and cirrhotic patients ( 4 , 23 , 24 ). In this study, the proportion of the NK cluster cells decreased significantly in the cirrhotic group, which was consistent with previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…The important role played by glutamate in HSCs in various liver diseases has been recently reported. Choi WM et al [27] . found that the uptake of glutamate was increased in activated HSCs and that mGluR5 activation enhanced the cytotoxicity of NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Different cell-targeted Erk pathways may play a heterogeneous role in the progression of fibrosis. In NK cells, mGluR5 regulates the expression of IFN-γ through Mek/Erk, thereby activating the cytotoxicity of NK cells to HSC and driving the resolution of liver fibrosis [ 42 ]. ALOX-5 relies on the Erk signal axis to promote the secretion of LTB 4 and LTC 4 to induce HSC activation.…”
Section: Discussionmentioning
confidence: 99%